Photodynamic inactivation of virulence factors of Candida strains isolated from patients with denture stomatitis - Pereira, Cristiane Aparecida [UNESP]; Domingues, Nádia [UNESP]; Silva, Michelle Peneluppi [UNESP]; Costa, Anna Carolina Borges Pereira [UNESP]; Junqueira, Juliana Campos [UNESP]; Jorge, Antonio Olavo Cardoso [UNESP] (Elsevier B. V., 2015)
Candida species are major microorganisms isolated in denture stomatitis (DS), an inflammatory process of the mucosa underlying removable dental prostheses, and express a variety of virulence factors that can increase their pathogenicity. The potential of Photodynamic inactivation (PDI) in planktonic culture, biofilms and virulence factors of Candida strains was evaluated. A total of 48 clinical Candida isolates from individuals wearing removable maxillary prostheses with DS were included in the study. The effects of erythrosine (ER, 200μM) and a green LED (λ 532±10nm, 237mW/cm(2) and 42.63J/cm(2)) in a planktonic culture were evaluated. The effect of the addition of ER at a concentration of 400μM together with a green LED was evaluated in biofilms. The virulence factors of all of the Candida strains were evaluated before and after the PDI process in cells derived from biofilm and planktonic assays. All of the Candida species were susceptible to ER and green LED. However, the biofilm structures were more resistant to PDI than the planktonic cultures. PDI also promoted slight reductions in most of the virulence factors of C. albicans and some of the Candida tropicalis strains. These results suggest that the addition of PDI is effective for reducing yeasts and may also reduce the virulence of certain Candida species and decrease their pathogenicity.
Keywords: Biofilms; Candida; Denture stomatitis; Photodynamic inactivation; Virulence factors